2013
DOI: 10.1002/ggge.20250
|View full text |Cite
|
Sign up to set email alerts
|

The composition and distribution of the rejuvenated component across the Hawaiian plume: Hf‐Nd‐Sr‐Pb isotope systematics of Kaula lavas and pyroxenite xenoliths

Abstract: [1] Rejuvenated volcanism refers to the reemergence of volcanism after a hiatus of 0.5-2 Ma following the voluminous shield building stage of Hawaiian volcanoes. The composition of the rejuvenated source and its distribution relative to the center of the plume provide important constraints on the origin of rejuvenated volcanism. Near-contemporaneous lavas from the Kaula-Niihau-Kauai ridge and the North Arch volcanic field that are aligned approximately orthogonally to the plume track can constrain the lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 121 publications
3
23
0
Order By: Relevance
“…Some samples display ilmenite exsolutions within garnet (including samples NMNH-114959-20A and 77SL-582 analyzed here), majorite pseudomorphs and nanodiamonds and probably initially crystallized at >5 GPa (>150 km) (Keshav and Sen, 2001;Keshav et al, 2007), deeper than the 80-90 km seismically defined base of the lithosphere beneath Oahu (Li et al, 2004). The radiogenic Hf and Nd isotopic compositions of the pyroxenites analyzed thus far (Bizimis et al, 2013, including the high pressure pyroxenite NMNH-114959-20A, place them at the depleted end of the OIB array, suggesting an origin from a depleted mantle source, distinct from the isotopically enriched "eclogitic" component inferred for the Hawaiian plume (Hauri, 1996;Huang and Frey, 2005).…”
Section: Samplesmentioning
confidence: 93%
See 4 more Smart Citations
“…Some samples display ilmenite exsolutions within garnet (including samples NMNH-114959-20A and 77SL-582 analyzed here), majorite pseudomorphs and nanodiamonds and probably initially crystallized at >5 GPa (>150 km) (Keshav and Sen, 2001;Keshav et al, 2007), deeper than the 80-90 km seismically defined base of the lithosphere beneath Oahu (Li et al, 2004). The radiogenic Hf and Nd isotopic compositions of the pyroxenites analyzed thus far (Bizimis et al, 2013, including the high pressure pyroxenite NMNH-114959-20A, place them at the depleted end of the OIB array, suggesting an origin from a depleted mantle source, distinct from the isotopically enriched "eclogitic" component inferred for the Hawaiian plume (Hauri, 1996;Huang and Frey, 2005).…”
Section: Samplesmentioning
confidence: 93%
“…A location map is provided in Appendix A. In this study we focus on previously studied, well-characterized spinel lherzolite and garnet pyroxenite xenoliths (Bizimis et al, 2013(Bizimis et al, , 2004Sen et al, 2011) as well as some newly reported samples. The samples are from the Dale Jackson and Dean Presnall collections at the Smithsonian Institution.…”
Section: Samplesmentioning
confidence: 99%
See 3 more Smart Citations